Investigating the causes of casing deformation induced by faults and natural fractures in shale gas platform wells - Juncheng Zhang; Jun Li; Wei Lian; Dian Wang; Shaokun Guo; Haoyong Huang; Junfeng Li (PLoS ONE, 2025)
During the development of deep shale gas in Luzhou, southern Sichuan, faults and natural fractures caused extensive casing shear deformation, including those that happen during hydraulic fracturing and those that occur prior to fracturing. To investigate the mechanism of complex deformation of platform well casings caused by faults and natural fractures, this paper analyzed the characteristics of casing deformation and identified the primary types of deformation. By integrating microseismic signal data, it was determined that fault slip is the direct cause of casing deformation. Based on these findings, the Mohr–Coulomb criterion was used to evaluate fault slip conditions, using critical pore pressure as a threshold. A finite element model of platform well fracturing was built with actual engineering parameters. Simulating the fracturing process showed how pore pressure changed under different fracture conditions. Comparing these results with the critical pore pressure clarified how fractures at different scales impact casing deformation in platform wells. The findings suggest that: (1) Casing deformation in the Luzhou Block mainly involves shear deformation, with fault or large-scale fracture slip being the direct cause of these shear deformations; (2) Fault slip at the well location caused casing deformation during fracturing, while fluid migration along faults caused fault instability and slip near non-fractured wells, leading to casing deformation before fracturing; (3) If fractures of a scale similar to the well spacing are present within the platform area, nearby wells may also deform before fracturing. These results provide a scientific basis for understanding casing deformation mechanisms in shale gas platform wells and for developing effective prevention and control measures in the Luzhou Block.